Pengaruh Konsumsi Listrik Dan Pembangunan Keuangan Terhadap Pertumbuhan Ekonomi ASEAN Aplikasi Data Panel ARDL - Nabila Rasha (Politeknik Kutaraja, 2022)
This study aims to analyze the influence of electricity and financial development on economic growth in ASEAN by using panel ARDL panel. Panel data in this study from 1999 to 2014 and covers 8 Countries, with a total of 140 samples. The results showed that electricity consumption and financial development dose not very effect on economic growth both the short and long run. Short-term influence is better rather than long-term.